Preliminary Adaptation and Validation of the Spq and the Ceq for the Study of Teaching Development Programmes in a Chilean University Context [Adaptación y Validación Preliminar del Spq y el Ceq Para el Estudio de la Formación en Docencia Universitaria en el Contexto Chileno] - Abricot-Marchant, N (Pontificia Universidad Catolica de Chile, 2016)
The aim of this study was to adapt the Course Experience Questionnaire (CEQ) and the Study Process Questionnaire (SPQ) and to provide preliminary evidence of their validity in the context of university teaching developmental programs. Content validity evidence was analyzed by 6 expert raters, internal structure was checked via confirmatory factor analysis, and internal consistency and correlation between the instruments were examined via alpha and omega coefficients. The convenience sample was composed of 686 students from a university located in the Metropolitan Region of Chile. Revised and linguistically adapted versions of the instruments were obtained. A high degree of agreement among the raters was observed regarding the contents of the instruments. The evidence obtained supported the 2-factor structure of the SPQ and the 4-factor structure of the CEQ. Also, theoretically consistent correlations were found according to the 3P model. For example, students with a deep learning approach perceived good teaching and clear objectives and goals. The possibility to develop arguments for the use of the CEQ and the SPQ based on other types of evidence is discussed. © 2016 by Psykhe.